BRAND AWARENESS AND PERCEIVED QUALITY POS EXPRESS PT POS INDONESIA - Senny Handayani Suarsa; Ferdinan Nainggolan; Prety Diawati (JABE (Journal of Applied Business and Economic), 2021)
The brand is an essential consideration in purchasing and the quality of the product or service. For this reason, the brand strategy and product quality are applied by PT. Pos Indonesia Lumban Julu Medan Branch to attract consumers. This study aimed to determine the effect of brand awareness and perceived quality on purchasing decisions for Pos Express package delivery services. Data were collected by survey method to 315 respondents through convenience sampling technique. As a result, there is no significant effect between brand awareness on purchasing decisions, but it significantly affects perceived quality.